Local Elections and Local Politics in Indonesia: Emerging Trends - Priyambudi Sulistiyanto (Centre for Asian Social Science Research (CASSR), Faculty of Social and Political Sciences, UIN Sunan Gunung Djati Bandung, 2020)
This article analyses local elections held in the post-Suharto era in Indonesia with a special reference to pilkada (pemilihan kepala daerah langsung [direct elections of local leaders]) between 2005 and 2008. Using the state-society perspective, it argues that local elections have seen the rise of new political dynamics and rapid growth of electoral activity in regions. Pilkada has brought about the emergence of coalitional politics, political ideologies or streams (aliran), the rise of ‘little kings’ (raja kecil), an increasing number of businesspeople entering local politics, the use of gangsters/goons (preman) in local elections, a boom in political consultancy, and the increase of the novote camp. There are grounds for optimism regxarding the intensity of the interaction between the local state and society in the regions. The people in the regions have now had the opportunities to vote for their leaders directly, something which was impossible in the past. There is no doubt that the electoral competition for candidates is going to be very important because the availability of good potential local leaders varies between the regions. Political parties themselves have to improve their performance and build a proper recruitment process so that they can find good candidates who can attract voters.